The Republic of Benin Diagnostic Trade Integration Study Update : From Rents to Competitiveness - World Bank Group (World Bank, Washington, DC, 2015)
The Government of Benin has requested an update of the 2005 Diagnostic Trade Integration Study and has asked the World Bank to take the leading role in this exercise. The update’s objectives are to (a) take stock of progress in the mainstreaming of trade in the government’s national development strategy and of implementation of the Action Matrix recommendations; (b) complement and deepen the analysis in selected areas; and (c) revise and update the Action Matrix to take account of the evolving context since 2006. The aim of the analysis is to assist the Government of Benin in defining an overall competitiveness strategy for inclusive, job-creating export-led growth in accordance with the key priorities identified in the 2013 Plan Stratégique de Développement du Commerce (PSDC), and to further mainstream trade into the general policy orientation defined by Benin’s key policy documents, including the Growth and Poverty Reduction Strategy Paper (GPRSP) update. The DTIS Update (DTISU) offers a diagnosis, analytical framework and action plan, giving trade expansion a key role in the reduction of poverty and vulnerability. As mandated by the Paris Principles, the DTISU’s approach is strongly aligned with the MICPME’s PSDC (Trade Development Strategy Plan, henceforth TDSP) and draws also from the diagnosis in the Government of Benin’s recent poverty assessment (INSAE 2014) as well as the 2011 update of the GPRSP. It emphasizes the linkages between poverty, jobs, and trade with two key objectives: (i) reducing poverty through trade-led growth, and (ii) reducing vulnerability.